Control of Inflation on the Road of the Accession to European Monetary Union. The Case of Albania - Bakalli, Grisida; Turan, Gungor; Imeraj, Erinda (European Scientific Journal, ESJ, 2017)
The aim of this paper is to analyze the monetary policy and inflation targeting applied by the Bank of Albania on the road to Euro adaption. There will be a comparison with the monetary policy used by the European Central Bank for the countries aiming to join the European Union and it will be shown if the Bank of Albania’s monetary policy rules adapt those of the ECBs. The data of inflation and exchange rates in the Albanian economy in 2005-2013 has been used. Since the variables are non-stationary and present unit roots, Johansen’s co-integration technique has been applied. This methodology has allowed for obtaining of a co-integrating relationship among variables in the long-run. The co-integration results provide evidence of a no co-integration. This indicates that inflation and exchange rate does not move together in Albania in the long-run. According to the test results, it can be said that in the long-run foreign currency does not main cause of inflation in Albania.